An Investigation of Mother Tongue Influence on EFL Learners during their Speaking Performance - Fitriani, Naria; Zulkarnain, Said Iskandar (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
This study aimed at investigating the mother tongue influence of Acehnese learners in vocational English class. The students? mother tongue influence can be detected by the results of speaking errors on their performance. The primary data of the students? speaking performance was recorded, then transcribed. Furthermore, the student?s questionnaire was applied to support the primary data. The results of this study were analyzed and presented into two parts containing pronunciation and grammar errors. Meanwhile, the data obtained from the questionnaire was quantitatively shown that the learning process of the target language was affected by the first language.